Language Attitudes of Dayak Ngaju Students toward the Use of Ngaju Language - Anastasia Tesalonika; Iis Nur Rodliyah; Alfina Khaidem (Universitas Brawijaya, 2022)
This study aims to reveal the Dayak Ngaju students’ attitudes towards their mother tongue, the Ngaju language, and the factors affecting the attitudes. Following Fasold (1984) and Jendra (2012), a qualitative analysis of interviews with selected subjects was conducted after the questionnaires were distributed to the respondents. The questionnaire respondents were 30 college students of Dayak Ngaju ethnicity, 9 of which were interviewed to corroborate their answers to the questionnaire. The results revealthe students’ positive attitudes towards the Ngaju language. The students’ positive attitudes were influenced by two factors: (a) the language's power and prestige, and (b) the language’s internal system. The respondents considered the Ngaju language as an important part of their community because the language reflects the Dayak Ngaju people’s cultural identity despite the challenges the speakers of the language might have when communicating in their mother tongue. Thus, language preservation is needed.